2016
DOI: 10.1371/journal.pone.0159657
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency and Also Transgenic Overexpression of Timp-3 Both Lead to Compromised Bone Mass and Architecture In Vivo

Abstract: Tissue inhibitor of metalloproteinases-3 (TIMP-3) regulates extracellular matrix via its inhibition of matrix metalloproteinases and membrane-bound sheddases. Timp-3 is expressed at multiple sites of extensive tissue remodelling. This extends to bone where its role, however, remains largely unresolved. In this study, we have used Micro-CT to assess bone mass and architecture, histological and histochemical evaluation to characterise the skeletal phenotype of Timp-3 KO mice and have complemented this by also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 57 publications
4
23
0
Order By: Relevance
“…Young's modulus values for the Timp-3 −/− bone demonstrated a tendency to decrease, but the high variance of these values resulted in no statistical significance compared with WT bone. The decrease in the mechanical properties of bone we observed in this study is in agreement with previous works that found compromised tissue quality and [26], cardiovascular [27], liver [10], and musculoskeletal tissue of Timp-3 −/− mice [15]. Alterations in the structure and composition of the Timp-3 −/− bone mice can explain the deficiencies observed in the mechanical properties of the Timp-3 −/− bone.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Young's modulus values for the Timp-3 −/− bone demonstrated a tendency to decrease, but the high variance of these values resulted in no statistical significance compared with WT bone. The decrease in the mechanical properties of bone we observed in this study is in agreement with previous works that found compromised tissue quality and [26], cardiovascular [27], liver [10], and musculoskeletal tissue of Timp-3 −/− mice [15]. Alterations in the structure and composition of the Timp-3 −/− bone mice can explain the deficiencies observed in the mechanical properties of the Timp-3 −/− bone.…”
Section: Discussionsupporting
confidence: 92%
“…The morphological analysis of Timp-3 −/− cortical bone revealed a significant decrease in the bone volume, with thinner cortices and higher canal porosity compared with WT bone. Timp-3 −/− bones were smaller, with a reduced cross-sectional area and altered geometry (I max , I min , and J), in agreement with previous studies conducted on the tibiae of the same mouse strain [15]. The increase in the Timp-3 −/− cortical bone porosity due to the vascular channels is also in agreement with the increase in angiogenesis typical of these bones [6].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations